The Analysis of Foreign Trade Activities of Russia and Asia-Pacific Region - Kuznetsova, Natalia Victorovna; Kocheva, Ekaterina Victorovna; Matev, Nikolay Anatolievich (International Journal of Economics and Financial Issues, 2016)
The development of foreign trade policy, adequate to market principles of functioning of the Russian economy and its consecutive integration to the world economy poses a major challenge for the researchers: the potential identifying for the increasing of mutual trade flows and their further integration. To assess the dynamics of foreign economic relations, we used the indicators of economic openness and the importance of mutual trade. In order of modelling the trade and economic integration of Far Eastern Federal District and the countries of Asia-Pacific region, we used gravity models in this study. Consequently, there have been built six gravity models that characterize the dependence of Russian Far Eastern export and import on countries of Asia-Pacific region for each period of the study. Design and the analysis of gravity models have revealed patterns of Far Eastern Federal District with Asia-Pacific countries as well as with the individual partner countries of the district. The dynamics of gravitational interactions defining the factors' relations is determined. Keywords: foreign trade turnover, gravity models, export, import, Asia-Pacific region, modelling, trade and economic integration. JEL Classifications: F100, F130